The electronic library Fundamentals and application (Journal of the College of Basic Education, 2022)
This study discusses the foundations of the electronic library in terms of concept, origin, development and importance.and basic components and human and material requirements, in an effort to reach results that would suggestScientific planning for the establishment of a comprehensive model electronic library in academic libraries, to meet the needsinformation to the community. The study included four main axes: 1: Introduction, 2. Theoretical framework-3, the procedural framework-4, discussion, conclusions and recommendations.